3-mind revolution - "Chiem, David; Caswell, Brian" (Singapore, 2016)
Award-winning authors David Chiem and Brian Caswell have written a brand new edition of their thought-provoking bestseller The 3-Mind Revolution. Building on its previous premise of preparing us for the world of tomorrow, it incorporates further extensive research into education, psychology, neuroscience and cyber technology, conducted over the past seven years since the release of their first edition.Relevant, informative and insightful in its approach, this new edition of The 3-Mind Revolution gives us more reason to adapt to a different kind of thinking today as it will determine our success or failure in the future.
Keywords: Cognition in children